Prevalence and Gene Expression Variation of Pathogenic Hemolysin Producing E. coli Isolated From Patients with Urinary Tract Infections and Diarrhea - Maath Thaer Nejres; Halah Abdulkhaliq Awadh (Tikrit Journal of Pure Science)
The hlyA gene in Escherichia coli (E. coli) bacteria codes for the protein hemolysin, which is a toxin produced by these bacteria and contributes to their ability to cause disease. Hemolysin is part of the bacteria's mechanism to increase their harmful effect by lysis red blood cells releasing hemoglobin. This toxin creates holes in the host cell membrane, leading to leakage of cell components and eventual death. The main objective of the current study is to investigate the presence and gene expression of hemolysin toxin genes in E. coli isolates from clinical infection cases, including samples from urinary tract infection and diarrhea from patients in Tikrit city, using real-time polymerase chain reaction (RT-PCR) technique. The study was carried out on 50 isolates, divided into 20 isolates from urinary tract infections, 20 isolates from diarrhea cases and 10 isolates as control samples (stool samples from healthy people without diarrhea). The overall prevalence of hemolysin in E. coli isolates was 18 out of 40 (45 %). The occurrence of hemolysin-producing E. coli isolates detected by RT-PCR was 10 out of 20 (50 %) in urinary tract infection samples and 8 out of 20 (40 %) in diarrhea samples. The production of the hemolysin toxin by E. coli isolates varies depending on the type of sample. The results also showed that the gene expression level of hemolysin gene was higher in cases of urinary tract infections compared to cases of diarrhea, with the gene expression level being (Mean folding = 5.933) in urinary tract infection cases, while it was (Mean folding = 3.712) in diarrhea cases, with significant differences at a probability level of (P value ≤ 0.05). The  results showed that the prevalence of the gene responsible for the secretion of hemolysin toxins by E. coli is higher in cases of urinary tract infection (UTIs) than in cases of diarrhea. and the gene expression level of the hlyA gene showed a significant increase in cases of urinary tract infections compared to cases of diarrhea.